Prognostic value of acute cor pulmonale in COVID-19-related pneumonia: A prospective study - Beyls, Christophe; Martin, Nicolas; Booz, Thomas; Viart, Christophe; Boisgard, Solenne; Daumin, Camille; Crombet, Maxime; Epailly, Julien; Huette, Pierre; Dupont, Hervé; Abou-Arab, Osama; Mahjoub, Yazine (Frontiers in Medicine, 2022)
Background: It is known that acute cor plumonale (ACP) worsens the prognosis of non-COVID-19 acute respiratory distress syndrome (NC-ARDS). The risk of ACP occurrence in mechanically ventilated patients with NC-ARDS is evaluated by the ACP risk score. To date, there is few data on risk factors and prognosis of ACP induced by COVID-19 pneumoniae. Objective: To evaluate the prognostic value of ACP, assessed by trans-thoracic echocardiography (TTE) and clinical factors associated with ACP in a cohort of patients with COVID-19 pneumoniae. Material and Methods: Between February 2020 and June 2021, patients admitted to Amiens University Hospital intensive care unit for COVID-19 related pneumonia were assessed by TTE within 48 hours of admission. ACP was defined as a right ventricle/left ventricle area ratio > 0.6 associated with septal dyskinesia. The primary outcome was mortality at 30 days. Results: Among 146 patients included, 36% (n=52/156) developed ACP of which 38% (n=20/52) were non-intubated patients. Classical factors of ACP in NC-ARDS such as PaCO2 > 48mmHg, driving pressure > 18 mmHg PaO2/FiO2 < 150 mmHg were not associated with ACP (all P> 0.1). The primary outcome occurred in 32 (22%) patients. More patients died in the ACP group (n=20/52 vs. n=12/94, P=0.001). On multivariable Cox analysis, ACP [hazards ratio (HR)=3.35 95%CI [1.56-7.18], P=0.002] and age > 65 years (HR=2.92 95%CI [1.50-5.66], P=0.002) remained independently associated with 30-day mortality. Conclusions: In a cohort of patients admitted in ICU for COVID-19 pneumonia, ACP was a frequent complication, even in non-intubated patients, that increased 30-days-mortality. Classical factors of ACP in NC-ARDS were not associated with ACP in COVID-19 pneumoniae.